2014
DOI: 10.1186/1471-2407-14-21
|View full text |Cite
|
Sign up to set email alerts
|

Risks of postoperative paresis in motor eloquently and non-eloquently located brain metastases

Abstract: BackgroundWhen treating cerebral metastases all involved multidisciplinary oncological specialists have to cooperate closely to provide the best care for these patients. For the resection of brain metastasis several studies reported a considerable risk of new postoperative paresis. Pre- and perioperative chemotherapy (Ctx) or radiotherapy (Rtx) alter vasculature and adjacent fiber tracts on the one hand, and many patients already present with paresis prior to surgery on the other hand. As such factors were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Yet, there was a statistical trend for a greater extent of the perifocal T2WI lesion in patients with a motor deficit (60.9 Ϯ 34.8 cm 3 ) compared with the others (38.1 Ϯ 27.2, P ϭ .08) (On-line Fig 2A). Cortical M1 representations (3.4 Ϯ 1.1 versus 3.6 Ϯ 0.8 cm 3 ) and the mean CST volumes (0.7 Ϯ 0.3 versus 0.5 Ϯ 0.2 cm 3 ) were of equal size between the 2 groups (P Ͼ .1) (On-line Fig 2B).…”
Section: Functional Tractography and Mr Imaging Volumetrymentioning
confidence: 82%
See 3 more Smart Citations
“…Yet, there was a statistical trend for a greater extent of the perifocal T2WI lesion in patients with a motor deficit (60.9 Ϯ 34.8 cm 3 ) compared with the others (38.1 Ϯ 27.2, P ϭ .08) (On-line Fig 2A). Cortical M1 representations (3.4 Ϯ 1.1 versus 3.6 Ϯ 0.8 cm 3 ) and the mean CST volumes (0.7 Ϯ 0.3 versus 0.5 Ϯ 0.2 cm 3 ) were of equal size between the 2 groups (P Ͼ .1) (On-line Fig 2B).…”
Section: Functional Tractography and Mr Imaging Volumetrymentioning
confidence: 82%
“…The deterioration of existing or newly developed motor deficits does not only reduces the quality of life but also reduces overall survival of the affected patients independent of the extent of resection and the adjuvant therapy. 3,29 Tumor size, location, and infiltrative growth patterns have been discussed as underlying causes of neurologic impairment in those patients. 5 Here, we found that patients with tumor masses directly within motor functional tissue as depicted by FET-PET or T1-CE merely accounted for approximately half of the patients with motor deficits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to current guidelines, surgery is recommended for symptomatic and accessible brain metastases followed by whole-brain irradiation or stereotactic irradiation [3 -6]. As surgery is a safe treatment according to a recent study, some risk factors such as location in an eloquent region or preoperative radiotherapy that may increase the risk of postoperative neurological deficits have to be considered preoperatively [7].…”
Section: Introductionmentioning
confidence: 99%